Penentuan Strategi Bisnis Dalam Meningkatkan Penjualan Roti Dengan Metode SWOT Dan QSPM - Rickhi Hidayat; Andung Jati Nugroho (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
XYZ is a factory that produces food in the form of bread (Bakery). Seeing the main problems in this company, namely experiencing fluctuations and difficulties for the company in developing its business to increase sales in its marketing strategy. For this reason, strategic business costs are needed to be able to overcome these problems. The purpose of this research is to determine the right business strategy for the company so that it becomes a consideration for the company to increase sales. For this reason, an analysis is carried out by applying the SWOT and QSPM methods. The SWOT method is used to determine the strategy, while the QSPM method is used to determine alternative business strategies that will be used by the company. After conducting the research, the results obtained from the IFAS matrix with a total score of strength = 1.53 and weakness = 1.21, a difference of 0.32 was obtained. While the results of the EFAS matrix with a total score of opportunities = 1.62 and threats = 0.9, a difference of 0.72 is obtained. From the IFAS and EFAS matrices, the SO strategy results are obtained: affordable prices, maximizing good service and product variety as well as employee training. WO: increasing marketing through online media, increasing prices, adding product innovation, and using technology as an advertising medium. ST: improve service quality, add product development, and maintain customer loyalty. WT : maximizing promotions, and optimizing the cost of workloads and more. The results of the alternative QSPM method strategy obtained show the highest score on the WO strategy with a TAS score: 6.39 namely increasing marketing through online media, increasing product prices by adding innovation, and using technology by making digital marketing target markets for advertising.